The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/jcm12062314
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Tolerability of Atropine Eye Drops for Myopia Control in Non-Asian Regions

Abstract: Myopia is the most common ocular disorder worldwide with an increasing prevalence over the past few decades. It is a refractive error associated with excessive growth of the eyeball. Individuals with myopia, especially high myopia, are prone to develop sight-threatening complications. Currently, atropine is the only drug that is used to slow myopia progression in clinical practice. However, there are still areas of uncertainty such as treatment strategy, optimal concentration when considering risk–benefit rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…While some studies reported an insufficient effect (statistically not different from the placebo group), 107 , 110 , 111 several recent studies indicate a notable reduction in axial length growth. 10 , 11 , 112 , 113 The frequency of application or dose may be increased when lower doses are proving ineffective. 107 …”
Section: Algorithmmentioning
confidence: 99%
“…While some studies reported an insufficient effect (statistically not different from the placebo group), 107 , 110 , 111 several recent studies indicate a notable reduction in axial length growth. 10 , 11 , 112 , 113 The frequency of application or dose may be increased when lower doses are proving ineffective. 107 …”
Section: Algorithmmentioning
confidence: 99%
“…Nevertheless, the optimal treatment regimen for atropine, particularly concerning dosage and duration has yet to be definitively established. Despite the widespread use of 0.01% atropine as the safest concentration for controlling myopia progression, conflicting evidence in the literature has emerged due to variations in treatment response [ 11 , 16 , 17 , 18 , 19 ]. For example, the results of a recent clinical trial showed that 0.01% atropine eye drops did not reduce changes in the spherical equivalent (SE) or axial length (AL) among children in the United States [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of initial clinical trials and studies investigating atropine for myopia management focused on Asian populations, several studies with atropine conducted in non-Asian children have also demonstrated variable efficacy 14 . As a result, there is an increasing adoption of Asian clinical trial protocols by ophthalmologists in Western countries.…”
Section: Introductionmentioning
confidence: 99%